Juridical Analysis Of Standard Clauses In The Binding Sale And Purchase Agreement Apartment (Apartment Unit) - Basyarudin (CV. AFDIFAL MAJU BERKAH, 2022)
Population density and land constraints require the provision of alternative places to live apart from the landed house. Not only for people who have excess money, but also for people from the bottom. Overcrowding often takes up land so that living space becomes limited and crowded. Moreover, the pedatang community is unstoppable in its presence. There are immigrants who live in a time that is not short. They even moved in as citizens. Big cities must be like that. Flats are one of the new alternatives to answer the above needs. As for the problem, How is the standard clause in the apartment sale and Purchase Agreement (PPJB) regulated in the legal system in Indonesia? To discuss the problems mentioned above, the research conducted descriptive analysis by describing and reporting in detail, and systematic and comprehensive about everything related to default in the implementation of the work agreement carried out by the contractor. Based on the results of the study, the standard clause is extensively used in the business world by business actors including in the sale of apartment units (SRS). PPJB widely uses standard contract / standard clauses for practical purposes but can be unbalanced in contracting and legal protection for apartment consumers based on the Menpera decision, Law No. 16 of 1985 as the basic rules governing the ownership of flats and Law No. 8 of 1999 on consumer protection, as well as KUHPerd. as the expected consumer protection of flats is compensation and not the element of removal. As stipulated in law No. 8 of 1999 provides legal protection for consumers of flats.